PEMERIKSAAN KADAR PROTEIN PADA SUSU SAPI SEGAR ASAL PETERNAKAN CILAWU KABUPATEN GARUT DENGAN METODE KJELDAHL - Dani Sujana (Jurnal Sains dan Teknologi Laboratorium Medik, 2020)
Milk as one of the results of livestock commodities is a food ingredient that is a source of nutrition or animal protein substances. Whole cow's milk must contain at least 3.25% of milk fat and 8.25% of nonfat milk solids. In this study, qualitative analysis of raw cow's milk samples for the determination of protein content was carried out using the biuret method and quantitative analysis using the Kjeldahl method. From the results of the biuret examination, a purple solution was obtained which showed a positive result containing protein. Quantitative results using the Kjeldahl method are NaOH with oxalic acid titration until the solution becomes a clear pink color. The average result obtained from the standardized titration of NaOH is 9.17. The result of analysis by quantitative titration is the reaction of HCl with NaOH and phenophthalein to form a clear pink color with an average of 9.3. The average yield of pure cow's milk protein content is 9.36%.